PENGARUH ZAT PENGATUR TUMBUH AUKSIN: INDOLE BUTIRIC ACID (IBA) DAN SITOKININ: BENZIL AMINO PURINE (BAP) dan KINETIN DALAM ELONGASI PERTUNASAN GAHARU (Aquilaria beccariana) - Mulyono, Daru (Jurnal Sains dan Teknologi Indonesia, 2010)
The objective of the research is to know the optimal formula of auksine and sitokinine in the Murashige dan Skoog (MS) basic media and to conserve gaharu tree (Aquilaria beccariana) in order to produce young gaharu plants which have similar properties with their mother plants. The research used Factorial Design with basic analysis of Complete Randomized Design in order to know the effect of treatment to the elongation. The results of the research showed that after 8 weeks of the treatment with IBA and the combination with BAP and Kinetin have significant effect to the increase of height and number of segment but have no significant effect to the number of buds. The combination of 0.1 mg/l IBA and BAP 0.05 mg/l was the optimal formula for the elongation of young gaharu plants with the increse of height 1.7 cm and number of segmnent 6.4.